Breaststroke training - Lawrence, M. (American Swimming Magazine, 1998)
This is the transcribed presentation of Mike Lawrence's Breaststroke Training Talk at the 1998 ASCA World Coaches Clinic on the theory and practical specifics of breastsroke training.